2021
DOI: 10.3390/en14185846
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Validation of Flow Uniformity Improvement by a Perforated Plate in the Heat Exchanger of SFR Steam Generator

Abstract: The steam generator in a nuclear power plant is a type of heat exchanger in which heat transfer occurs from the hot fluid in multiple channels to the cold fluid. Therefore, a uniform flow over multiple channels is necessary to improve heat exchanger efficiency. The study aims at experimentally investigating the improvement of flow uniformity by the perforated plate in the heat exchanger used for a sodium-cooled fast reactor stream generator. A 1/4-scale experimental model for one heat exchanger unit with 33 × … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…where, β is the average ratio of the velocity or temperature, which can be calculated by Equation (17), and β i is the flow rate or temperature ratio, which is defined by Equation (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…where, β is the average ratio of the velocity or temperature, which can be calculated by Equation (17), and β i is the flow rate or temperature ratio, which is defined by Equation (18).…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [17] reviewed the utility of the porous baffle and confirmed that the porous baffle reduced the mal-distribution by 1/3 compared to the prototype baffle. Kim et al [18] considered using a multi-porous plate to ensure a uniform flow rate distribution of a heat exchanger used in a sodium-cooled fast reactor (SFR) steam generator. The improvement of flow uniformity and pressure drop through the use of multi-porous plates was confirmed through experiment and analysis.…”
Section: Introductionmentioning
confidence: 99%